TO THE QUESTION ABOUT PLATELET REPRODUCTION IN VITRO - Kondrashev, S.A. (World of Medicine and Biology, 2012)
It is shown during research, in process of reproduction in vitro platelets are capable for the building of new cells structures to use not only cholesterol, plasma proteins, amino acids, but also some fractions of other cells – erythrocytes, leukocytes.